PENGARUH PEMBERIAN TEPUNG Azolla sp DENGAN DOSIS BERBEDA TERHADAP PERTUMBUHAN BENIH IKAN NILA GIFT ( Oreochromis sp ) - KOMARIYAH .; HADI PRANGGONO; ARIS ADHI PRASETYO (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
Gift tilapia (Oreochromis sp.) Is one type of fish which are potential to be cultivated intensivelybecause tilapia gift has favorable properties, namely: rapid growth, eating all the food (omnivores),high tolerance to various environmental conditions, and resistant to disease attacks. Seeing the potential of the plant Azolla sp. which is a pest in agricultural land which is very abundant anduntapped by the community then the Azolla sp. used as a natural alternative feed on tilapia seedgift, because the high protein content and amino acid composition essensialnya complete. Thisresearch was conducted in August to September 2010, housed at the Laboratory of AquacultureFaculty of Fisheries University of Pekalongan. With the aim to determine the effect of feeding onthe growth of Azolla sp tilapia gift. The research was conducted based on completely randomizeddesign with 4 treatments and 3 replications. The treatments applied were given doses of naturalfood Azolla sp, ie A = 2%, B = 4%, C = 6%, and D = 8%. Results obtained from the study is oftreatment D showed the highest growth in average body weight with average seed weight 2.81 g,followed by treatment C, B and A, each with average seed weight 1.19 g, 1.71 g, 2.41 g Theanalysis showed that differences in the dose range of Azolla sp very real effect on the growth oftilapia seed gift. While the results of Orthogonal Polynomial analysis showed D treatment weresignificantly different with treatment C, B, A. The water quality of the media during the studywithin reasonable range, the temperature between 29-32 º C, pH ranged from 7.0 to 7.2 and DOranges from 3-5 ppt.Keywords: Azolla sp., alternative feed, Gift tilapia